2014
DOI: 10.1183/09031936.00131614
|View full text |Cite
|
Sign up to set email alerts
|

Real-life use of long-acting antimuscarinic agents following their approval for COPD treatment

Abstract: Chronic obstructive pulmonary disease (COPD) pharmacological treatment aims to reduce symptoms, represented mostly by dyspnoea and its impact on daily life, and future risk, i.e. lung function decline, mortality and exacerbations [1]. Inhaled therapies, including long-acting bronchodilators (LABD) and inhaled corticosteroids (ICS), are the main treatments recommended for COPD patients. LABD have been found not only to improve lung function, decrease dyspnoea, increase exercise tolerance and improve health stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Similar to our results, the authors found that in 32.5% of cases, the new LAMA was added to LABA/ICS as triple therapy and very infrequently used as monotherapy 17. Also in the UK, the most frequent pathway to triple therapy was the addition of a LAMA to the existing treatment with a LABA/ICS 18.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our results, the authors found that in 32.5% of cases, the new LAMA was added to LABA/ICS as triple therapy and very infrequently used as monotherapy 17. Also in the UK, the most frequent pathway to triple therapy was the addition of a LAMA to the existing treatment with a LABA/ICS 18.…”
Section: Discussionsupporting
confidence: 88%
“…However, review of these recommendations prompts the suggestion that simplification of diagnostic criteria, particularly for primary care physicians, could significantly enhance patient identification and initiation of care. This is an important issue since multiple studies from Europe have indicated that COPD is greatly underdiagnosed [ 1 , 26 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies revealed a high degree of overtreatment with respiratory medication, in particular with inhaled corticosteroids (ICS), in patients with COPD and especially in GOLD groups A and B. [1][2][3][4][5] Despite the narrow indication for the prescription of ICS in COPD, their use has been reported in up to 70% of patients in some European countries, such as Switzerland, Greece, and the UK. [6][7][8] In line with this, data from the COSYCONET COPD cohort also showed that about 2/3 of patients received an inhaled corticosteroid, though this would have been indicated in only about 50% according to GOLD 2017 recommendations.…”
Section: Introductionmentioning
confidence: 99%